PENERAPAN PEMBELAJARAN LANGSUNG BERBANTUAN MEDIA KOMPUTER UNTUK MENINGKATKAN KEMAMPUAN PENALARAN DAN MOTIVASI BELAJAR SISWA - Sudianto Pasaribu; Hasratuddin Hasratuddin; Dian Armanto (JURNAL TEMATIK, 2019)
The study aims to know the application of direct learning assisted by computer media to improve the reasoning ability and learning motivation of Madinatussalam private Madrasah Tsanawiyah students. This type of research is classroom action research with data collection techniques through observations of tests of mathematical reasoning ability, teacher and student activities, and student motivation questionnaires. Based on the results of the study found: (1) the use of direct learning assisted by computer media can increase student motivation in learning mathematics in the first cycle by 66.61%, in the second cycle by 79.56%. (2) the use of direct learning assisted by computer media can increase students' mathematical reasoning ability in learning mathematics circle material I by 40.00%, cycle II 85.71%, and (3) class completeness has increased towards mathematics learning by 45.71 %. Thus it can be concluded that an increase in motivation and ability in mathematical reasoning students circle material through the use of direct learning assisted by computer media in class VIII MTs Private Madinatussalam District Percut Seituan District